2005
DOI: 10.1080/13880200590919384
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS Analysis of Chloroform Extracts in Flowers, Stems, and Roots ofTripleurospermum callosum.

Abstract: The chemical composition of the chloroform extracts of flowers, stems, and roots of Tripleurospermum callosum (Boiss. & Heldr) E. Hossain growing along the northeastern coast of Turkey was studied by gas chromatographymass spectrometry (GC-MS). The GC-MS analyses of the chloroform extracts from air-dried parts of T. callosum yielded the identification of 93 compounds. These compounds were separated into eight classes that were terpenes-terpenoids, hydrocarbons, alcohols, acids, oxygen-containing compounds, ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 2 publications
0
21
1
Order By: Relevance
“…[50] screened the bioactive components of Plectranthus amboinicus leaves using GC-MS. GC-MS analysis of extract of Plectranthus amboinicus leaves found that they also contained celidoniol (nonacosane) as the dominant component. While [41] and [51] found that the plant extracts used in their studies contain less docosane (0.17 % and 0.29 %, respectively), a high amount of docosane was obtained in the present study (45.34 %). This suggests that using the plant in areas where the docosane molecule is frequently used will be advantageous.…”
Section: Resultscontrasting
confidence: 50%
“…[50] screened the bioactive components of Plectranthus amboinicus leaves using GC-MS. GC-MS analysis of extract of Plectranthus amboinicus leaves found that they also contained celidoniol (nonacosane) as the dominant component. While [41] and [51] found that the plant extracts used in their studies contain less docosane (0.17 % and 0.29 %, respectively), a high amount of docosane was obtained in the present study (45.34 %). This suggests that using the plant in areas where the docosane molecule is frequently used will be advantageous.…”
Section: Resultscontrasting
confidence: 50%
“…The selection of variables represents the primary metabolites in the PLS-DA score plot based on the VIP value (>1.0) and p -value (<0.05). The identification of metabolites was examined on the basis of retention times, retention indices of reported metabolites [22,23,24,25,26,27,28], and mass fragmentation patterns, with reference to the National Institute of Standards and Technology (NIST) library.…”
Section: Resultsmentioning
confidence: 99%
“…The two first compounds were also detected in the chloroform extracts of flowers, stems, and roots of T. callosum (Boiss. & Helder) E. Hossain, but in amounts less than 1% [8].…”
mentioning
confidence: 97%